Students’ Perceptions of the Use of Group Discussions Method in Teaching Basic Oral Communication at SMAN 1 Gerung - Kahar, Abdul; Wilian, Sudirman; Lail, Husnul (Program Studi Pendidikan Bahasa Inggris, 2025)
This research examines the effects of group discussions as a teaching method on improving students' basic oral communication skills, focusing on their perceptions, challenges, and outcomes. Conducted with 36 eleventh-grade students at SMAN 1 Gerung, this study utilized a mixed methods research design. Data was collected through a structured questionnaire, which included both closed-ended and open-ended questions to provide comprehensive insights. The findings reveal that group discussions have a significant positive effect on students’ speaking skills, particularly in vocabulary acquisition, fluency, pronunciation, and comprehension. In addition, group discussions encouraged active participation and engagement. However, challenges such as limited discussion time, nervousness, and unequal participation among students were also identified. Based on these findings, it is recommended that group discussions be integrated more frequently into speaking lessons. Deeper insights may be obtained for future studies by increasing the sample size and incorporating different teaching strategies, like project-based learning or digital tools. In general, this study highlights how group discussions enhance students' oral communication abilities in English classes.